A participação internacional das organizações não governamentais por meio de redes sociais: a rede brasileira pela integração dos povos - Neves, Maíra Junqueira (2007)
This research seeks to observe the international participation of a specific sector of civil society through social networks. Because of the amount of actors inside this group, Non Governmental Organizations (NGOs) have been chosen as the object of this dissertation. For that, it was also necessary to choose a Brazilian Network protagonist, which could be an example of the strength of this way of action, and for that reason Rebrip (The Brazilian Network for the Integration of Peoples) was picked. To obtain the necessary information for these intended studies, analysis was done of network documents and interviews with some representative members, who could speak knowingly about this actor and NGO involvement. The text demonstrated how social networks work and their importance to the NGOs and vice versa. As a main goal to give support to this text it was considered necessary to interpret the international changes in the last few years, that have occurred mainly in the economical, political, social, and cultural dimensions, as well as how these changes happen in modern states. A central element of this study is the possibility of a critical view of globalization, by academic expertise and also by the movement that questions it, called by many globalization authors the counter-hegemony globalization movement. Finally, it shows the connection between Rebrip and this movement, the importance of the networks for the international participation of NGOs and the difficulties that they face trying to put in practice their beliefs